2009
DOI: 10.1021/jm900688v
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic 2-(Thio)ureidocarboxylic Acids As a New Family of Modulators of Multidrug Resistance-Associated Protein 1: Synthesis, Biological Evaluation, and Structure−Activity Relationships

Abstract: Four series of aromatic carboxylic acids were prepared with a urea or thiourea moiety at the neighboring position to the carboxyl group and benzene or thiophene as aromatic scaffold. Using a calcein AM assay, these compounds were evaluated as inhibitors of multidrug resistance-associated protein 1 (MRP1) and selected compounds were examined toward P-glycoprotein (P-gp) as well as breast cancer resistance protein (BCRP) to assess selectivity for MRP1. Two 2-thioureidobenzo[b]thiophene-3-carboxylic acids (48, 49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 77 publications
0
21
0
Order By: Relevance
“…In 2009, our working group also presented aromatic 2‐(thio)ureidocarboxylic acids as novel lead for MRP1 inhibition, using the cDNA‐transfected human ovarian carcinoma cell line 2008/MRP1 and the calcein AM assay. The benzene moiety led only to weak inhibitors in the moderately low double‐digit concentration range, while a naphthyl partial structure (compound 16; Figure ) showed at least moderate inhibitory activity (IC 50 = 5.38 μM).…”
Section: Synthetic Compounds and Hts Resultsmentioning
confidence: 99%
“…In 2009, our working group also presented aromatic 2‐(thio)ureidocarboxylic acids as novel lead for MRP1 inhibition, using the cDNA‐transfected human ovarian carcinoma cell line 2008/MRP1 and the calcein AM assay. The benzene moiety led only to weak inhibitors in the moderately low double‐digit concentration range, while a naphthyl partial structure (compound 16; Figure ) showed at least moderate inhibitory activity (IC 50 = 5.38 μM).…”
Section: Synthetic Compounds and Hts Resultsmentioning
confidence: 99%
“…Recent studies have shown that thiourea functionality imparted greater inhibitory activity toward MRP1 in a series of drug derivatives relative to P-gp or BCRP, which is consistent with different types of binding. 43 …”
Section: Resultsmentioning
confidence: 99%
“…A number of MRP1 modulators whose mechanism of inhibition is poorly characterized have been reported. 95,96 In many cases, including the reference inhibitor leukotriene antagonist MK571, studies suggest that the mechanism of action relies on competitive inhibition. 97,98 Although MK571 was able to completely reverse vincristine resistance of MRP1-overexpressing cells, the required concentrations were too high to be used in vivo.…”
Section: Compounds Targeting Multidrug-resistant Cells Overexpressingmentioning
confidence: 99%